Quantitative cell-free circulating EGFR mutation concentration is correlated with tumor burden in advanced NSCLC patients. (July 2017) - Zhu, Yan-juan; Zhang, Hai-bo; Liu, Yi-hong; Zhang, Fu-li; Zhu, Ya-zhen; Li, Yong; Bai, Jian-ping; Liu, Li-rong; Qu, Yan-chun; Qu, Xin; Chen, Xian; Li, Yan; et al.
Highlights: Plasma EGFR status by ddPCR displayed sufficient accordance with tumor. Higher plasma EGFR mutation concentration correlated with more metastatic sites. Higher plasma EGFR mutation concentration correlated with extensive tumor burden. Abstract: Objectives: Droplet digital polymerase chain reaction (ddPCR) has shown sufficient concordance in detecting plasma epidermal growth factor receptor ( EGFR ) status in non-small cell lung cancer (NSCLC), compared to tumor tissues. However, the clinical significance of the quantitative plasma mutated EGFR concentration remains unknown. The purpose of this study was to explore the relationship of plasma mutated EGFR concentration with tumor burden in advanced NSCLC patients. Materials and methods: Using ddPCR, plasma DNA samples prior to administration of therapies from 113 consecutive NSCLC patients were analyzed for EGFR L858R substitution and deletion of exon19 (ex19del). Plasma EGFR status was compared to tumor EGFR status to determine concordance. Then, we assessed the correlation of plasma mutated EGFR concentrations with tumor burden and other tumor characteristics. Results and conclusion: Compared to tumor EGFR, the concordance rate of plasma and tissue EGFR status was 86.73%. Of the 64 patients who harbored tumor EGFR mutation, plasma mutated EGFR concentrations significantly correlated with number of metastatic sites (Spearman's r = 0.4954, p < 0.0001), number of lesions (Spearman's r = 0.4484, p = 0.0002), and sum of measurable lesions' diameters (Spearman's r = 0.3539, p = 0.0048). Number of metastatic sites was independently associated with mutated EGFR concentration in multiple linear regression. Besides, plasma mutated EGFR concentrations were significantly higher in those with extensive tumor burden (median concentration, 386.9 vs. 13.4 copies/mL; p < 0.0001) and stage IV disease (median concentration, 244.2 vs. 0 copies/mL; p = 0.0252). In conclusion, mutated plasma EGFR concentration determined by ddPCR analysis significantly correlated with tumor burden.